SHARIA ECONOMIC DISPUTE SETTLEMENT AT THE SYAR'IYAH COURT OF BANDA ACEH AND LHOKSEUMAWE - Friatna, Ida (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2024)
Contracts that occur between the parties often end in disputes that result in conflicts and disputes, thus requiring legal settlement. Settlement of sharia economic disputes can be done through litigation (religious court/syar'iyah court) or through non-litigation (arbitration). This study wants to find answers to the following questions: what are the reasons behind the occurrence of sharia economic disputes?; How is the authority and mechanism of the syar'iyah court to resolve sharia economic disputes? and are there any obstacles faced by the Syar'iyah Court of Banda Aceh and the Syar'iyah Mahkamah of Lhokseumawe in resolving sharia economic cases?. The research method uses a qualitative approach and the type of juridical normative-juridical empirical research. Data collection is done by interview. The results obtained from the research that has been carried out are that there are several factors behind the occurrence of sharia economic disputes, including breaking promises/waning achievements and there are acts against the law/getting out of contracts/agreements between the parties. Regarding the authority of the syar'iyah court, in accordance with Law Number 3 of 2006 amendments to Law Number 7 of 1989 concerning the Religious Courts, in which the authority of the Religious Courts/Syar'iyah Courts is added to the settlement of sharia economic cases. Regarding the mechanism for resolving sharia economic disputes, it is guided by material law and applicable formal law. Furthermore, in resolving sharia economic cases, the Syar'iyah Court of Banda Aceh and the Syar'iyah Court of Lhokseumawe did not encounter significant obstacles. Because sharia economic cases are still few compared to cases that are under the authority of other Sharia Courts.